2016
DOI: 10.1111/issr.12092
|View full text |Cite
|
Sign up to set email alerts
|

Health care privatization processes in Europe: Theoretical justifications and empirical classification

Abstract: This article analyses the health care system reform process in Europe based on the concept of privatization. This notion is understood from two perspectives. First, privatization may concern the health care financing or the provision of health services. Second, privatization can be "imposed" on individuals or be "internalized" and then introduced by individuals (patients and doctors). So we emphasize the diversity that privatization can assume. We classify privatization mechanisms used by different countries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“… 1 It can take different forms, including privatising services provision and health care finance, or transferring ownership from public to private. 2 , 3 Early efforts to privatise health care systems started in developed countries; since then, developing countries have taken cues from them to privatise their health care systems. 4 , 5 International agencies, such as the World Bank, play a major role in supporting privatisation in low-income developing countries, 5 and countries in Europe 2 , Latin America 6 and Asia 7 , 8 have seen privatisation as the solution for overcoming the financially burdened, inefficient and unsatisfactory public health care systems.…”
mentioning
confidence: 99%
“… 1 It can take different forms, including privatising services provision and health care finance, or transferring ownership from public to private. 2 , 3 Early efforts to privatise health care systems started in developed countries; since then, developing countries have taken cues from them to privatise their health care systems. 4 , 5 International agencies, such as the World Bank, play a major role in supporting privatisation in low-income developing countries, 5 and countries in Europe 2 , Latin America 6 and Asia 7 , 8 have seen privatisation as the solution for overcoming the financially burdened, inefficient and unsatisfactory public health care systems.…”
mentioning
confidence: 99%
“…The reconfiguration of the socialised and private financing of healthcare in France represents a political decision that has transformed the role of national and complementary health insurance. Understanding this means, in the first instance, identifying the theoretical and ideological principles of the movements towards the privatisation of healthcare systems (André et al 2016), in particular the various strategies for competition that can be identified in the recent transformations undergone by the Bismarckian health insurance schemes (Hassenteufel and Palier 2007), and an institutional complementarity between the two major types of health insurance (3.1.). The first term enables several successive governments of different political parties to contribute to this reconfiguration by sharing a single representation of the problems facing the French health insurance system and therefore the solutions to be employed to resolve them.…”
Section: A Political Option That Redefines the Distribution Of Welfare Resourcesmentioning
confidence: 99%
“…Indeed, and since the 1980s, one can note a stagnation of the share of health spending paid for by NHI. This shift coincides with the first mentions in reports and legal texts of the field of “complementary health insurance,” a field that “should be organized and regulated.” The creation of CMU‐C and UNOCAM is seen as institutionalizing this “scrambling” trend by reinforcing the integration between private and public insurance—and offering the basis for further disengagement from the public sphere. Without necessarily rejecting this interpretation, other specialists insist that PHI homogenization and recognition have been paralleled by a process of “statization” or “technocratization” of NHI governance .…”
Section: French Private Health Insurance: a Review Of Recent Reformsmentioning
confidence: 99%